2006
DOI: 10.1063/1.2206811
|View full text |Cite
|
Sign up to set email alerts
|

The role of coherent structures in subgrid-scale energy transfer within the log layer of wall turbulence

Abstract: The present effort documents the relationship between dominant subgrid-scale energy transfer events and coherent motions within the log layer of wall turbulence. Instantaneous velocity fields in the streamwise-wall-normal plane of a zero-pressure-gradient turbulent boundary layer acquired by particle-image velocimetry at Re ϵ u * ␦ / = 2350 are spatially filtered to generate an ensemble of resolved-scale velocity fields in the spirit of large-eddy simulation. The relationship between subgrid-scale dissipation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 38 publications
8
42
4
Order By: Relevance
“…Numerical results (3D LES) by Taylor et al (2005) also support the previously described trends in <uw>. (2000) and Natrajan and Christensen (2006). These packets align coherently in the streamwise direction to generate large regions of uniform streamwise momentum deficit, which maintain coherence over large streamwise distances.…”
Section: Investigation Of the Intermittent Motions With Quadrant Decosupporting
confidence: 67%
See 1 more Smart Citation
“…Numerical results (3D LES) by Taylor et al (2005) also support the previously described trends in <uw>. (2000) and Natrajan and Christensen (2006). These packets align coherently in the streamwise direction to generate large regions of uniform streamwise momentum deficit, which maintain coherence over large streamwise distances.…”
Section: Investigation Of the Intermittent Motions With Quadrant Decosupporting
confidence: 67%
“…This dynamical arrangement creates multiple uniform momentum zones and lower velocity toward the wall. The vertical extent of these structures, or packets, is about 0.6H, with H the water depth, and the streamwise length is about 1.5H (Natrajan and Christensen 2006). The size of the individual hairpin vortices varies.…”
Section: Investigation Of the Intermittent Motions With Quadrant Decomentioning
confidence: 99%
“…The presence of backscatter is thought to play an important role on the local dynamics of the turbulent flow. For example, recent experimental studies have shown that in turbulent boundary layers strong backscatter and forward-scatter events occur in the leading and trailing edges, respectively, of inclined vortical (hairpin-like) structures (Carper and Porté-Agel 2004;Natrajan and Christensen 2006). In LES, SFS transfer rates of resolved kinetic energy are especially important since the reproduction of their mean values has been shown to be a necessary condition for a simulation to produce accurate higher-order velocity statistics (Meneveau and Katz 2000).…”
Section: Les and Sfs Modellingmentioning
confidence: 98%
“…It may be said that the reduction of the turbulent shear stress and the turbulent energy by filtering is related more to losing of the vortex structure than the streak structure. Natrajan & Christensen 43) also showed that the vortex structures are important in energy transfer between the filtered and sub-filter scale flow.…”
Section: Filtering Of Flow Over Flat Smooth Surfacementioning
confidence: 99%